Quantification of Postdiagnosis Cancer Patient Navigation - Posani, Sarojini; Burnette, Ursula J; McClelland, 3rd, Shearwood (American journal of clinical oncology, 2025)
Patient navigation is a key component in achieving optimal cancer care outcomes. While a vast amount of literature suggests its clear benefits in cancer care, limited objective data exists regarding navigation metrics, specifically the number of navigator-patient contacts and time spent with patients. This study attempts to attain findings from the published literature to better understand navigation metrics to achieve optimal cancer care outcomes. A systematic PubMed search was performed in April 2025 focusing on cancer patient navigation, with the term "patient navigation or navigator in postdiagnosis cancer care-contact metrics." Important metrics analysed were the median number of navigator-patient contacts, the median time spent per patient, the most common barriers addressed, and their respective improved outcomes. These metrics were then compared with results from the ongoing Phase I Navigator-Assisted Hypofractionation (NAVAH) trial (clinicaltrials.gov, NCT05978232). A total of 7 peer-reviewed studies met the inclusion criteria. The number of patient-navigator contacts widely ranged from 1 to 119; the average being 13.4 (∼0.3 times/mo, compared with 2 times/mo in NAVAH). The median time spent per patient varied from 40 minutes to over 10 hours (compared with 20 mins/encounter in NAVAH). The most commonly discussed topic was financial assistance, which is consistent with NAVAH findings. Improved outcomes were significantly reduced treatment interruption days and securing early specialist appointments. As previously published data depicted wide variability, it highlights the need for standardized data collection and reporting practices, as such quantitative data can facilitate the evolution of patient navigation in achieving improved cancer care outcomes.